Effect of using a hemostatic gelatin sponge versus a dense polytetrafluorethylene membrane for socket sealing following immediate implant placement: a randomized clinical study - Mahmoud Shalash; Aalaa Emara (Bulletin of the National Research Centre)
Abstract Background Socket sealing following flapless immediate implant placement involves placing a barrier membrane to prevent the ingrowth of bacteria or contaminants to the dental implant during the early phase of healing. Dense Polytetrafluorethylene membranes have been the gold standard socket sealing barrier due to their impermeability to the oral flora, which allows for undisturbed implant healing. The search for a more cost-efficient material for sealing the socket without compromising implant osseointegration was sought. This study aims to evaluate the effectiveness of socket sealing after immediate implant placement in the premolar/molar region using a gelatin sponge, as opposed to a dense Polytetrafluorethylene membrane, and its impact on clinical implant osseointegration. Materials and methods The study was conducted on 20 patients, comprising 12 males and 8 females with an age range of 25–60 years. Those meeting the eligibility criteria of immediate implant placement were selected and divided equally into two groups. A control group, where an immediate implant and a dense polytetrafluorethylene membrane were used, and a test group where an immediate implant and a gelatin sponge was used. Exclusion criteria included smokers, presence of systemic or metabolic conditions, or a local pathology that would contraindicate implant placement. Teeth were extracted using a flapless approach. Implants were placed, and sockets were sealed using the allocated barrier. In the control group, the membrane was removed after 4 weeks. For the test group, the gelatin sponge was left to resorb spontaneously. After 4 months, implants were uncovered, and a 30 N/cm reverse torque test was applied to assess the clinical osseointegration. Results All implants healed uneventfully, without any radiographic evidence of bone loss. There was no clinical or radiographic difference between the outcomes in the control and the test groups. For the 20 dental implants subjected to a 30 N/cm reverse torque test, clinical integration was observed. Conclusion Within the limitations of this study, both dense polytetrafluorethylene membranes and gelatin sponges are effective methods for socket sealing, allowing for successful osseointegration following flapless immediate implant placement in posterior sites, with gelatin sponge offering easier handling and a reduced cost compared to dense polytetrafluorethylene. A larger study sample to verify the outcomes of this stud is recommended.